Pancreatic Endocrine Tumors: A Report on a Patient Treated with Sorafenib - Jeong, Hee Kyoung; Roh, Sang Young; Hong, Sook Hee; Won, Hye Sung; Jeon, Eun Kyoung; Shin, Ok Ran; Lee, Su Lim; Ko, Yoon Ho (Journal of Korean medical science, 2011)
A 31-yr-old man with abdominal pain was diagnosed with a pancreatic endocrine tumor and multiple hepatic metastases. Despite optimal treatment with interferon alpha, a somatostatin analog, local therapy with high-intensity focused ultrasound ablation for multiple hepatic metastases, and multiple lines of chemotherapy with etoposide/cisplatin combination chemotherapy and gemcitabine monotherapy, the tumor progressed. As few chemotherapeutic options were available for him, sorafenib (800 mg/day, daily) was administered as a salvage regimen. Sorafenib was continued despite two episodes of grade 3 skin toxicity; it delayed tumor progression compared to the previous immunotherapy and chemotherapy. Serial computed tomography scans showed that the primary and metastatic tumors were stable. Thirteen months after beginning targeted therapy, and up to the time of this report, the patient is well without disease progression. We suggest that sorafenib is effective against pancreatic endocrine tumors.